Finite element modeling of the linear friction welding of GH4169 superalloy. (15th December 2015) - Yang, Xiawei; Li, Wenya; Li, Jinglong; Xiao, Bo; Ma, Tiejun; Huang, Zhe; Guo, Jia
Abstract: In the present paper, finite element method (FEM) simulation of linear friction welding (LFW) GH4169 superalloy was carried out using ABAQUS software. The friction coefficients of GH4169 superalloy under different parameters (friction load, friction velocity and specimen temperature) were obtained using the friction and wear experiments. A two-dimensional (2D) coupled thermo-mechanical model was established. Using this model, the temperature fields of GH4169 superalloy during LFW process was firstly investigated. Based on the shearing and extrusion deformations during LFW process, the mises stress and the equivalent plastic strain fields of LFW GH4169 superalloy at different welding times were studied. The actual LFW process of GH4169 superalloy was recorded using a high speed camera. The surface temperature fields of joint were experimentally observed using an infrared thermal imaging instrument. Axial shortening and macroscopic morphology of linear friction welded joint obtained from experiments validated the simulation results. Finally, by consideration of the temperature fields of the simulated welded joint, the authors experimentally investigated the microstructure of the actual welded joint. Graphical abstract: Highlights: Two dimensional FEM was created to simulate the LFW process of GH4169 superalloy. Shear stress in the initial stage is the dominant, while extrusion force dominates in the late stage. FEM was validated by experiments (axial shortening, flash shapes and joint color difference). The average value of grain size in the weld zone is smaller than that in other regions.